2012
DOI: 10.1038/bjc.2012.433
|View full text |Cite
|
Sign up to set email alerts
|

Processed meat consumption and risk of cancer: a multisite case–control study in Uruguay

Abstract: Background:The role of processed meat in the aetiology of several cancers was explored in detail.Methods:In the time period 1996–2004, a multisite case–control study was conducted in Montevideo, Uruguay. The study included 6 060 participants (3 528 cases and 2 532 controls) corresponding to cancers of the oral cavity, pharynx, oesophagus, stomach, colon, rectum, larynx, lung, female breast, prostate, urinary bladder, and kidney (renal cell carcinoma only).Results:The highest odds ratios (ORs) were positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 17 publications
3
48
0
1
Order By: Relevance
“…De Stefani E reported that consuming salted meat, another kind of processed foods, was associated with higher risk of squamous cell carcinoma of esophagus, no matter in one-site or multi-site case control studies (De Stefani et al, 1999;De Stefani et al, 2003;De Stefani et al, 2009). In Netherland, one cohort study also presented the similar association between processed meat and ESCC, with the HR being 3.47 (Keszei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…De Stefani E reported that consuming salted meat, another kind of processed foods, was associated with higher risk of squamous cell carcinoma of esophagus, no matter in one-site or multi-site case control studies (De Stefani et al, 1999;De Stefani et al, 2003;De Stefani et al, 2009). In Netherland, one cohort study also presented the similar association between processed meat and ESCC, with the HR being 3.47 (Keszei et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with studies conducted in the Uruguay population, which focused specifically on salted meat consumption. 21,22 Salted meat preparation and consumption were a long tradition in the Yanting area. Preserving meat and food with salt was a main way because there were no refrigerators available in such rural areas until the recent decade.…”
Section: Discussionmentioning
confidence: 99%
“…But, findings from previous studies on the associations between processed meat and ESCC were not consistent. [13][14][15][16][17][18] A varied definition of processed meat might partially explain the inconsistency of the results. 19 A recent literature review reported that processed meat was significantly associated with esophageal adenocarcinoma, but not with ESCC.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…45 [18]. A study by De Stefani et al [19] assessed CRC risk and processed meat consumption using a multisite case-control design in 6,060 participants in Uruguay. A positive association was found for CRC with high consumption of processed meat (OR 2.39, 95% CI 1.76-3.24) [19].…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%